Pengaruh Penerapan Model Blended-Problem Based Learning terhadap Kemampuan Berpikir Kritis Pesrta Didik pada Materi Asam dan Basa - Darsef Darwis; Arif Rahman; Maulana Latif (LPPM Universitas Negeri Jakarta, 2020)
acids and bases topics. Quasy experiment was chosen as research method with posttest only group design. The research population was students of XI IPA 1 and XI IPA 2 in SMA Negeri 26 Jakarta. The sample was established using the purposive sampling technique by choosing two classes as experiment class and control class. The experiment class was taught by using the Blended-Problem Based Learning model, while the control class was taught by using Blended-Explicit Instruction. The data were collected by using critical thinking skill questions. The data analysis technique used independent sample t test. The result showed that the experiment class’s mean was 68,306, while the control class was 58,611. The hypothesis was obtained by value of tcalculate (3,454) > ttable (1,667) with significant level is 0,05. So, it can be concluded that there was positive effect of Blended-Problem Based Learning model on students’ critical thinking skill in acids and bases topics. Keywords Blended-Problem Based Learning, Critical Thinking Skills, Acids and Bases